The mediating role of TQM and organizational excellence, and the moderating effect of entrepreneurial organizational culture on the relationship between ERP and organizational performance. Issue 6 (10th October 2016) - Al-Dhaafri, Hassan Saleh; Al-Swidi, Abdullah Kaid; Yusoff, Rushami Zien Bin
Abstract : Purpose: The purpose of this paper is to investigate the relationship between enterprise resource planning (ERP) and organizational performance through examining the mediating effect of total quality management (TQM) and organizational excellence and the moderating effect of entrepreneurial organizational culture (EOC). Design/methodology/approach: A survey questionnaire was used to collect the data from Dubai Police Departments. Out of the questionnaires distributed, 320 completed usable were returned and used for the analysis which employed partial least squares structural equation modelling methodology. Findings: The results showed that there are positive and significant relationships between ERP, organizational excellence, TQM, and organizational performance. In addition, TQM was found to partially mediate the effect of ERP on organizational performance, where organizational excellence was found to fully mediate the effect on the same relationship. However, the moderating role of EOC on the ERP, TQM, and organizational performance was not confirmed. Practical implications: Several practical implications have been gained from this study. It will increase the awareness of managers and decision makers to consider the constructs test to enhance the overall organizational performance in their organizations. The role of TQM and organizational excellence to facilitate the implementation of ERP is very critical. In addition, this research will increase the awareness of different stakeholders such as customers, supplier, and shareholders to integrate the proposed constructs examined to enhance the overall organizational performance. Originality/value: The current study is one of the few or the only empirical study that examines the joint effect of ERP, TQM, organizational excellence, and EOC on organizational performance.